Identifying therapeutic targets for schizophrenia - Karli Montague-Cardoso (Nature Portfolio, 2021)
There is a continual need to develop new therapies for neuropsychiatric disorders such as Schizophrenia, and identifying the underlying molecular processes remains challenging. Chadha et al. recently discovered a potential role for mTOR kinase activity disruption in Schizophrenia and further uncover the precise pathomechanism. Their study sheds further light on the role of mTOR in Schizophrenia and could inform the development of future therapeutic strategies for the condition.